Tissue Engineering and Photodynamic Therapy: A New Frontier of Science for Clinical Application -An Up-To-Date Review - Aires-Fernandes, Mariza; Amantino, Camila Fernanda; do Amaral, Stéphanie Rochetti; Primo, Fernando Lucas (Frontiers in Bioengineering and Biotechnology, 2022)
Tissue engineering (TE) connects principles of life sciences and engineering to develop biomaterials as alternatives to biological systems and substitutes that can improve and restore tissue function.The principle of TE is the incorporation of cells through a 3D matrix support (scaffold) or using scaffold-free organoid cultures to reproduce the 3D structure. In addition, 3D models developed can be used for different purposes, from studies mimicking healthy tissues and organs as well as to simulate and study different pathologies. Photodynamic therapy (PDT) is a non-invasive therapeutic modality when compared to conventional therapies. Therefore,PDT has great acceptance among patients and proves to be quite efficient due to its selectivity, versatility and therapeutic simplicity. The PDT mechanism consists of the use of three components: a molecule with higher molar extinction coefficient at UV-visible spectra denominated photosensitizer (PS), a monochromatic light source (LASER or LED) and molecular oxygen present in the microenvironment. The association of these components leads to a series of photoreactions and production of ultra-reactive singlet oxygen and reactive oxygen species (ROS). These species in contact with the pathogenic cell, leads to its target death based on necrotic and apoptosis ways. The initial objective of PDT is the production of high concentrations of ROS in order to provoke cellular damage by necrosis or apoptosis. However, recent studies have shown that by decreasing the energy density and consequently reducing the production of ROS, it enabled a specific cell response to photostimulation, tissues and/or organs. Thus, in the present review we highlight the main 3D models involved in TE and PS most used in PDT, as well as the applications, future perspectives and limitations that accompany the techniques aimed at clinical use.